Superradiance of an ensemble of nuclei excited by a free electron laser. Issue 3 (March 2018) - Chumakov, Aleksandr; Baron, Alfred; Sergueev, Ilya; Strohm, Cornelius; Leupold, Olaf; Shvyd'ko, Yuri; Smirnov, Gennadi; Rüffer, Rudolf; Inubushi, Yuichi; Yabashi, Makina; Tono, Kensuke; Kudo, Togo; et al.
Abstract In 1954 Dicke predicted the accelerated initial decay of multiple atomic excitations1, laying the foundation for the concept of superradiance. Further studies2–4 suggested that emission of the total energy was similarly accelerated, provided that the system reaches the inversion threshold. Superradiant emission of the total energy has been confirmed by numerous studies4–12, yet the acceleration of the initial decay has not been experimentally demonstrated. Here we use resonant diffraction of X-rays from the Mössbauer transition13 of57 Fe nuclei to investigate superradiant decay, photon by photon, along the entire chain of the de-excitation cascade of up to 68 simultaneous coherent nuclear excitations created by a pulse of an X-ray free-electron laser. We find agreement with Dicke's theory1 for the accelerated initial decay as the number of excitations is increased. We also find that our results are in agreement with a simple statistical model, providing a necessary baseline for discussing further properties of superradiance, within and beyond the low-excitation regime. Multiphoton superradiance is observed in a nuclear system excited by an X-ray free-electron laser. Tracking the system decay photon by photon shows strong enhancement of the first photon's decay rate, in good agreement with Dicke's formulation.